Solitary sterile neonatal liver abscess in an infant - Ahmed, Minhajuddin; Chowdhary, Sona; Kumar, Abhay; Ali, Manal Ashraf (International Journal of Contemporary Pediatrics, 2017)
Neonatal liver abscess is rare clinical entity. There should be strong index of suspicion in preterm and term neonates with indwelling catheters and unidentifiable focus. A differential diagnosis should be kept in mind in these patients. Surgical and antimicrobial led to a favorable outcome.